Accuracy evaluation of a numerical simulation model of nasal airflow. (May 2014) - Lu, Jiuxing; Han, Demin; Zhang, Luo
Abstract: Conclusion: Our numerical simulation model provides an accurate reflection of nasal airflow, and the results were validated by clinical measurements. Objectives: To evaluate the accuracy of a numerical simulation model of nasal airflow. Methods: Ten volunteers with normal nasal cavities underwent CT, acoustic rhinometry, and rhinomanometry. CT data were uploaded into Mimics, ICEM-CFD, Fluent, and CFD-Post software for three-dimensional modeling, finite element grid division, transient calculations, and analysis, respectively. Velocity and pressure data of airflow were obtained during the normal respiratory cycle. The accuracy of the simulation was evaluated by two methods: acoustic rhinometry measurements were used to evaluate the accuracy of the anatomic model, and rhinomanometry measurements were used to evaluate the accuracy of the nasal resistance values obtained by numerical simulation. Results: There were no significant differences between the values describing the model and the acoustic rhinometry measurements, the nasal resistance values obtained by numerical simulation. The airflow through the nasal cavity was mainly laminar. The maximum velocities were measured at the nasal valve, the amplitudes of all velocity curves at locations beyond the nasal valve were reduced. The amplitudes of the pressure curves increased from the front to the back of the airway.